O uso de tecnologia assistiva no auxílio ao idoso diabético - Oliveira, Alexandre Faraco de (2013)
Diabetes mellitus is a typical disease of aging that has presented a progressive increase in its prevalence in the population throughout the world and especially in Brazil. Among the diabetic patients, the elderly, tend to be the group who is the most affected by complications resulted from the disease. These complications have tried to be studyed those related to diabetic foot, in particular those associated with peripheral neuropathy and injuries arising from it. We were able to check the impact of diabetic foot neuropathic involvement and on the health of a population that were hospitalized patients and we note the predominant involvement of elderly people as well as the large number of mutilations caused by the treatment, which has resulted in a big cost to the health care system, without saving the patients, in comparison to the low cost of an Assistive Technology for prevention. Also we appreciate the peaks of plantar pressure in a group of elderly people with neuropathy and measured the ability of a device to Assistive Technology, the footwear for diabetics, to reduce these pressure peaks, the factor contributed to the genesis of plantar lesions. The shoes for diabetics were shown to be able to significantly reduce the pressure peaks in static or dynamic analysis. Thus we can conclude that the Assistive Technology, as footwear for diabetics, are a valid option in an effort to reduce the peaks of plantar pressure, and in this way protect the feet of elderly diabetic neuropathy. This protection not only can be beneficial to reduce the morbidity and mortality of the disease but also in order to reduce costs of treatment